ChatGPT as a catalyst for Critical and Creative Thinking (Práxis Educativa, 2025)
To address the current demands for the development of skills and dispositions in Critical and Creative Thinking (CCT), the CCT Learning Model was designed using a Generative Artificial Intelligence model—ChatGPT—for high school students. The Model (CCT_GenAI) encompasses six stages, in which ChatGPT acts as a mentor, tool, and simulator. This study aims to characterize the students through the application of a Critical and Creative Thinking Test and a Scale of Critical Thinking Dispositions, and to understand how skills and dispositions evolve after implementing the CCT_GenAI model. The study was conducted in Portugal, involving 23 12th-grade students. The students demonstrated a high initial level of CCT skills and dispositions, as well as a moderate improvement in skills and a significant increase in dispositions, particularly among students with lower initial scores.Keywords: Problem solving. Critical and Creative Thinking Learning Model. Generative Artificial Intelligence.